Exploring Tinnitus-Induced Disablement by Persistent Frustration in Aging Individuals: A Grounded Theory Study - Dauman, Nicolas; Erlandsson, Soly I.; Albarracin, Dolorès; Dauman, René (Frontiers in Aging Neuroscience, 2017)
Background: Qualitative research can help to improve the management of patients, meet their expectations and assist physicians in alleviating their suffering. The perception of moment-to-moment variability in tinnitus annoyance is an emerging field of exploration. This study sought to enlighten variability in tinnitus-induced disablement using a qualitative approach. Methods: Twelve participants (6 females, 6 males, aged 51-79) were recruited via the French Tinnitus Association Journal for participation in recorded semi-structured interviews. Each participant had three interviews lasting one hour, the sessions being separated one from the other by two weeks. Following recommendations of Charmaz (2014), the second and third interviews were aimed at gathering rich data, by enhancing the participants' reflexivity in the circumstances of distress caused by tinnitus. After transcription, the data (n=36 interviews) were analysed using the approach to Grounded Theory proposed by Strauss and Corbin (1998). Results: Tinnitus as persistent frustration emerged as being the core category uniting all the other categories of the study. Hence, the core category accounted for the broader scope in participants' experience of chronic tinnitus. It is suggested that tinnitus-induced disablement varied according to the degree of frustration felt by the participants in not being able to achieve their goals. The implications of this were analysed using the following categories: 'Losing body ownership', 'Lacking perspectives' and 'Persevering through difficulties'. Based on these findings, we draw a substantive theory of tinnitus tolerance that promotes an active, disciplined and individualized approach to tinnitus-induced disablement. The model distinguishes pathways from sustained suffering to reduced annoyance (i.e. emerging tolerance). It accounts for difficulties that the participants experienced with a perceived unchanged annoyance over time. Furthermore, this model identifies a set of new attitudes toward oneself and others that tinnitus tolerance would entail. Conclusion: The subjective experience of frustration enlighten tinnitus-induced disablement, offering new perspectives for long-term self-management. Modulation of frustration, rather than moderation of tinnitus interference, is suggested as a new approach to the clinical management of tinnitus-related distress.